Medical titanium-zinc alloy as well as preparation method and application thereof

By using porous pure titanium scaffolds and metal permeability methods to fill pure zinc in traditional bone implant materials, the problem of insufficient titanium elastic modulus and zinc mechanical strength is solved, and bone tissue healing and transplantation are achieved The strength of the incoming bond is improved and zinc ions are safely released in the body, meeting the needs of bone growth and repair.

CN119114962APending Publication Date: 2024-12-13HOSPITAL OF STOMATOLOGY CHINA MEDICAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311483019.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional bone implant materials such as pure titanium and pure zinc have insufficient mechanical properties and biocompatibility. The high elastic modulus and bioinergicity of titanium cause bone implants to fall off, and the insufficient mechanical strength of zinc cannot meet clinical needs.

Method used

The porous pure titanium bracket is prepared by selective laser melting technology, and the pure zinc powder is filled with metal melting method to form a titanium zinc alloy material, combining the ultrasonic treatment of hydrofluoric acid, nitric acid and distilled water and high-purity argon temperature-raising treatment to form a three-dimensional Titanium zinc alloy material with interoperable structure.

Benefits of technology

Improve the mechanical properties of the implant, promote bone tissue healing, enhance the binding strength of bone tissue and implant, and release zinc ions in the body through the biological activity characteristics of zinc, meeting the needs of bone growth and repair, ensuring that The safety and practicality of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004538740710000011
    Figure HDA0004538740710000011
  • Figure HDA0004538740710000012
    Figure HDA0004538740710000012
  • Figure HDA0004538740710000013
    Figure HDA0004538740710000013
Patent Text Reader

Abstract

The invention relates to a medical titanium-zinc alloy and a preparation method and application thereof.The medical titanium-zinc alloy comprises a porous pure titanium support and a pure zinc block, and the interior of the porous pure titanium support is of a three-dimensional intercommunication structure; and the pure zinc blocks are filled into gaps of the porous pure titanium bracket in a metal infiltration manner to form the titanium-zinc alloy material. According to the invention, through 3D printing of the pure titanium porous scaffold, the designed intraosseous fixation device promotes the osteogenesis performance in a living body by utilizing the biological activity characteristic of pure zinc metal; meanwhile, the pore diameter of the pure titanium porous scaffold is adjustable, so that the mechanical properties of different medical materials can be met. In addition, in the implanting process, the growth speed of bones can be better matched with the degradation speed of zinc; and finally, after implantation, along with continuous degradation of a zinc-containing phase in the material in an in-vivo environment, formation of a new bone is gradually induced, the new bone grows into a porous structure, and finally a titanium-bone interlocking structure is formed, so that the bonding strength between a bone tissue and an implant is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a medical titanium-zinc alloy and a preparation method and application thereof, which are mainly used in bone trauma surgery, repair and reconstruction surgery, and plastic surgery, and belong to the technical field of medical biomaterials. Background Art

[0002] Pure titanium is used in orthopedics as internal fixation plates and screws. It has high corrosion resistance, good biocompatibility and high safety, and rarely causes adverse tissue reactions. However, titanium has poor ductility and fatigue resistance, and its elastic modulus is higher than that of natural bone tissue, which easily produces stress shielding and causes bone implants to fall off. In addition, it is a bioinert material and lacks bone tissue induction. The current use of porous structures can improve the high elastic modulus of pure titanium so that it matches bone tissue. In addition, porous structures are conducive to the growth of new bone around it, which can increase the bonding strength between the implant and bone tissue. However, the porous structure also reduces the mechanical properties of metal materials, making them unable to withstand large loads, and their application is subject to certain restrictions.

[0003] Zinc, as an essential trace element for the human body, plays an important role in the growth and development of the body and the immune system, nervous system, and metabolic system. Zinc has good degradability, excellent biocompatibility, and antibacterial and osteogenesis effects, making it a potential bone implant. However, pure zinc alone as an absorbable bone implant has poor mechanical properties, with a compressive strength of less than 20MPa and an elongation of only 0.2%, which is far from meeting clinical needs. Therefore, in response to the above problems, it is urgent to develop a medical titanium-zinc alloy with excellent performance. Summary of the invention

[0004] Purpose of the present invention:

[0005] In order to overcome the shortcomings of traditional bone implant materials, a medical titanium-zinc alloy and its preparation method and application are provided to solve the problems of high elastic modulus and biological inertness of titanium and insufficient mechanical strength of zinc, so as to promote or guide the healing of bone tissue.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A medical titanium-zinc alloy, characterized in that it comprises a porous pure titanium stent and pure zinc powder, wherein the interior of the porous pure titanium stent is a three-dimensional interconnected structure; the pure zinc powder is filled into the gaps of the porous pure titanium stent by metal infiltration to form a titanium-zinc alloy material.

[0008] A method for preparing a medical titanium-zinc alloy comprises the following steps:

[0009] S1: Pure titanium powder is made into a porous pure titanium stent using selective laser melting technology;

[0010] S2: The porous pure titanium stent in S1 is placed in a mixed solution of hydrofluoric acid, nitric acid and distilled water, treated with an ultrasonic oscillator for 30 seconds to remove the unfused titanium powder on the surface, and then cleaned with anhydrous ethanol;

[0011] S3: placing a porous pure titanium support in a crucible, placing a pure zinc block on top of the support, introducing high-purity circulating argon gas by metal molten infiltration, heating to 650-700°C, maintaining for 1-1.5 hours, and then cooling to room temperature with the furnace;

[0012] S4: After demoulding, a titanium-zinc alloy blank is obtained, and the alloy is cut into shape along the outer boundary of the porous pure titanium bracket.

[0013] As a further description of the above scheme, in step S1, the medical pure titanium powder is aerosolized pure titanium powder, which is nearly spherical in shape and has a diameter of 15-53 μm; in the laser melting, the powder layer thickness is set to 30 μm, the power is set to 80 W, the laser spot diameter is set to 50 μm, and the scanning speed is set to 600 mm / s.

[0014] As a further description of the above scheme, in step S1, the internal unit cell of the porous pure titanium bracket is a rhombic dodecahedron, and the diameter and length of the prism in each unit are set to 300 μm and 900 μm respectively; the pore size of the porous pure titanium bracket is set to 500-1500 μm, and the porosity is 30%-80%.

[0015] As a further description of the above scheme, in step S2, the mixed aqueous solution of hydrofluoric acid, nitric acid and distilled water is prepared in a ratio of 1:4:5, the porous pure titanium bracket is placed in the mixed aqueous solution of hydrofluoric acid, nitric acid and distilled water and treated with an ultrasonic oscillator for 30 seconds.

[0016] As a further description of the above scheme, in step S3, the step of metal molten infiltration is as follows: place a porous pure titanium bracket in a crucible, and isolate the bracket with graphite paper except for the top; place a pure zinc block on the bracket and cover it with graphite paper; place the crucible on a steel plate, adjust it to a horizontal state, and push it into the furnace to a suitable position. Close the furnace door and test the air tightness. Vacuum for 15 minutes, pump in argon, and close the air inlet valve when the barometer reaches 0, repeat 3 times; adjust the boiler parameters: the starting temperature is 50°C, the temperature is raised to 650-750°C, the heating time is 2 hours, the insulation time is 1-1.5 hours, and then the temperature is lowered to 50°C.

[0017] As a further description of the above scheme, the titanium-zinc alloy blank described in step S4 is cut and formed according to the shape of the pure titanium porous bracket; it is polished with 800, 1000, 1500 and 2000 sandpaper in sequence, and then cleaned with anhydrous ethanol ultrasonic vibration, and blown dry for use.

[0018] An application of the above-mentioned medical titanium-zinc alloy, wherein the medical titanium-zinc alloy is applied to bone defect repair, bone reconstruction or bone replacement in orthopedic clinics.

[0019] Advantages and effects

[0020] 1. The present invention reduces stress shielding by 3D printing a porous bracket of pure titanium to ensure that the mechanical properties of the implant meet the load-bearing requirements; at the same time, the biological activity characteristics of pure zinc metal are utilized to enable the designed bone fixation device to promote osteogenesis in vivo.

[0021] 2. The present invention utilizes the adjustable pore size of the pure titanium porous scaffold to further optimize the mass ratio of titanium and zinc to meet the mechanical properties of different medical materials. In addition, the growth rate of the bone and the degradation rate of zinc can be better matched during the implantation process.

[0022] 3. After implantation, the zinc-containing phase in the material of the present invention continuously degrades in the body environment, gradually inducing the formation of new bone and growing into the porous structure, and finally forming a titanium-bone interlocking structure, thereby increasing the bonding strength between the bone tissue and the implant. The implant continuously restores the porous structure, which is also conducive to bone conduction.

[0023] 4. Safety and good practicality. Zinc plays an important role in many biochemical functions of the human body, including cell division, cell growth, wound healing and carbohydrate decomposition. Medical titanium-zinc alloy releases zinc ions required by the human body under the physiological environment in the body. The concentration of zinc ions released by the alloy is within the required range for biomedical use. Therefore, the medical titanium-zinc alloy medical device of the present invention is safe and has great advantages and application prospects.

[0024] 5. The preparation cost of the present invention is low and can meet the requirements of most bone filling, bone repair and bone transplantation applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a picture of a medical titanium-zinc alloy according to an embodiment of the present invention;

[0026] Figure 2 This is a SEM image of the medical titanium-zinc alloy prepared according to an embodiment of the present invention;

[0027] Figure 3 This is an XRD image of the medical titanium-zinc alloy material according to an embodiment of the present invention;

[0028] Figure 4 The proliferation of hDPSCs cells after being cultured with extracts of different dilution multiples according to the embodiment of the present invention;

[0029] Figure 5 The morphology and extension of hDPSCs cells after being cultured with extracts of different dilution multiples according to the embodiments of the present invention. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] The components of the embodiments of the present invention generally described and shown in the drawings herein may be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention.

[0033] The present invention provides the following technical solution:

[0034] A medical titanium-zinc alloy comprises a porous pure titanium stent and pure zinc powder, wherein the interior of the porous pure titanium stent is a three-dimensional interconnected structure; the pure zinc powder is filled into the gap of the porous pure titanium stent by metal infiltration to form a titanium-zinc alloy material. The advantages of the present invention are as follows: 1. After the product of the present invention is implanted, as the zinc-containing phase in the material is continuously degraded in the body environment, the formation of new bone is gradually induced and grows into the porous structure, and finally a titanium-bone interlocking structure is formed, thereby increasing the bonding strength between the bone tissue and the implant. The implant continuously restores the porous structure, which is also conducive to bone conduction. 2. It is safe and practical. Zinc plays an important role in various biochemical functions of the human body, including cell division, cell growth, wound healing and carbohydrate decomposition. The medical titanium-zinc alloy releases zinc ions required by the human body under the physiological environment in the body. The concentration of zinc ions released by the alloy is within the required range for biomedical use. Therefore, the medical titanium-zinc alloy medical device of the present invention is safe and has great advantages and application prospects.

[0035] A method for preparing a titanium-zinc alloy material comprises the following steps:

[0036] S1: Pure titanium powder is made into a porous pure titanium stent using selective laser melting technology;

[0037] S2: Place the porous pure titanium stent in S1 into a mixed solution of hydrofluoric acid, nitric acid and distilled water, treat with an ultrasonic oscillator for 30 seconds to remove the unfused titanium powder on the surface, and then wash with anhydrous ethanol to ensure the consistency of pore size and porosity;

[0038] S3: placing a porous pure titanium support in a crucible, placing a pure zinc block on top of the support, introducing high-purity circulating argon gas by metal molten infiltration, heating to 650-700°C, maintaining for 1-1.5 hours, and then cooling to room temperature with the furnace;

[0039] S4: After demoulding, a titanium-zinc alloy blank is obtained, and the alloy is cut into shape along the outer boundary of the porous pure titanium bracket.

[0040] The present invention reduces stress shielding by 3D printing a porous scaffold of pure titanium, ensuring that the mechanical properties of the implant meet the load-bearing requirements; at the same time, the biological activity characteristics of pure zinc metal are utilized to promote the bone formation performance of the designed bone fixation device in vivo; at the same time, the pore size of the pure titanium porous scaffold is adjustable, and the mass ratio of titanium and zinc can be further optimized to meet the mechanical properties of different medical materials. In addition, during the implantation process, the growth rate of the bone and the degradation rate of zinc can be better matched.

[0041] In step S1 of the embodiment of the present invention, the medical pure titanium powder is aerosolized pure titanium powder, which is nearly spherical in shape and has a diameter of 15-53 μm; under the conditions of laser melting technology: the powder layer thickness is set to 30 μm, the power is set to 80 W, the laser spot diameter is set to 50 μm, and the scanning speed is set to 600 mm / s.

[0042] In step S1 of the embodiment of the present invention, specifically, the porous pure titanium stent is a cylinder with a size of φ11mm×31mm. The internal porous structure is a rhombic dodecahedron, and each stent is composed of a 10×10×25 unit array with a size of 1.2mm×1.2mm×1.2mm. The diameter and length of the prism in each unit are set to 300μm and 900μm, respectively. The pore size is set to 500-1500μm, and the porosity is 30%-80%. The rhombic dodecahedron structure is a common unit cell structure of porous metal materials for orthopedic implants, which is similar to the structure of trabecular bone and is closer to the mechanical properties of human bones. In addition, the rhombic dodecahedron can achieve complete internal space filling.

[0043] In step S2 of the present invention, the mixed aqueous solution of hydrofluoric acid, nitric acid and distilled water is prepared in a ratio of 1:4:5. The pickling method is: the pickling solution is prepared by using hydrofluoric acid, nitric acid and distilled water, the hydrofluoric acid accounts for 10% of the total mass of the pickling solution, the nitric acid accounts for 40% of the total mass of the pickling solution, and the rest is distilled water, and the pickling time is 30 seconds. Pickling can remove residual metal powder on the surface and obtain a smooth and uniform surface.

[0044] In step S3 of the embodiment of the present invention, the step of molten metal infiltration is as follows: place a porous pure titanium bracket in a crucible, and isolate the bracket with graphite paper except for the top; place a pure zinc block on the bracket and cover it with graphite paper; place the crucible on a steel plate, adjust it to a horizontal state, and push it into the furnace to a suitable position. Close the furnace door and test the air tightness. Vacuum for 15 minutes, pump in argon, and close the air inlet valve when the barometer reaches 0, repeat 3 times; adjust the boiler parameters: the starting temperature is 50°C, the temperature is raised to 650-750°C, the heating time is 2 hours, the insulation time is 1-1.5 hours, and then the temperature is lowered to 50°C.

[0045] The titanium-zinc alloy blank in step S4 of the embodiment of the present invention is cut into a cylinder according to the shape of a pure titanium porous bracket, with a diameter of 10 mm and a height of 30 mm; it is polished in sequence with 800, 1000, 1500 and 2000 sandpaper, then cleaned with anhydrous ethanol ultrasonic vibration, and blown dry for use.

[0046] The mass ratio of titanium to zinc in the present invention is 0.8:1-2:1, which realizes the controllable distribution of titanium and zinc elements inside the material and the mechanical properties of titanium-zinc alloys with different mass ratios, so as to meet the growth and metabolism requirements of bone tissues in different positions, and at the same time, matches the bone growth rate with the zinc degradation rate.

[0047] An application of the above-mentioned medical titanium-zinc alloy, wherein the medical titanium-zinc alloy is used for bone defect repair, bone reconstruction or bone replacement in orthopedic clinics.

[0048] Example 1

[0049] A method for preparing a titanium-zinc alloy material:

[0050] Step 1: Use 3D printing to make a cylindrical pure titanium porous stent with a diameter of 12 mm and a thickness of 30 mm. Use distilled water, anhydrous ethanol, and acetone to ultrasonically clean the pure titanium porous stent, blow dry and set aside. Figure 1 As shown in A.

[0051] Step 2: Cut the pure zinc into a 100×50×30 mm cuboid, clean it with distilled water, anhydrous ethanol, and acetone ultrasonically, and blow dry it for later use.

[0052] Step 3: Pad the inner wall and bottom wall of the crucible with graphite paper, place the pure titanium porous bracket in the crucible, and isolate each bracket with graphite paper. Place the treated pure zinc block on the bracket and cover it with graphite paper. Put an insulation plug in the crucible in the furnace. Place the crucible on the steel plate, adjust it to a horizontal state, and push it to a suitable position in the furnace. Put another insulation plug outside the crucible, close the furnace door, and test the air tightness. After 15 minutes of vacuuming, pump in high-purity argon gas, close the air inlet valve when the barometer reaches 0, vacuum for another 15 minutes, pump in high-purity argon gas, and close the air inlet valve when the barometer reaches 0. Adjust the boiler parameters: start at 50℃, heat up to 650℃, heat up time 2 hours, keep warm time 1 hour, and then cool down to 50℃. The heating and cooling rate is 5℃ / min. After 15 minutes of vacuuming, pump in argon gas. When the barometer reaches 0, open the outlet valve, open the water tank, and start heating. Observe the pressure gauge and bubble speed every hour, and turn off the argon bottle after the temperature drops. Open the boiler the next day and take out the crucible and sample.

[0053] Step 4: After demoulding, the titanium-zinc alloy blank is obtained. The large blank is cut into a φ11mm×31mm cylinder according to the outer boundary of the porous bracket, and then the cylinder is cut into several discs with a diameter of 10mm and a thickness of 2mm. Each disc is then sanded to 2000 mesh. Figure 1 As shown in B.

[0054] In step 1, electron beam melting rapid prototyping technology is used to prepare a cylindrical porous pure titanium stent with a diameter of 12 mm and a thickness of 30 mm. Figure 1 A. The average pore size of the above-mentioned bracket is 550 μm, and the porosity is about 60%. The bracket has a honeycomb-like structure, and the pores are interconnected and penetrate the outer surface of the bracket, and have three-dimensional connectivity.

[0055] In step 3, pure zinc is filled into the pores of the porous titanium alloy stent by a metal molten pressureless infiltration method. Figure 1 B. The mass ratio M of titanium and zinc is estimated based on the porosity. Ti / M Zn =3 / 7. Scanning electron microscopy shows the microstructure of the three-phase metal interface of the material, such as Figure 2 As shown in the figure, it can be seen that the interface between pure titanium and pure zinc forms an alloy region with a thickness of 40-60μm, and there are no defects such as voids on the interface. Pure zinc is completely filled into the three-dimensional pores of the porous titanium alloy stent and forms a good metallurgical bond, ensuring the mechanical properties of the metal material. Through XRD technical analysis, the alloy phase formed by titanium and zinc is Ti3Zn 22 and TiZn3, such as Figure 3 shown.

[0056] The biosafety of the material was observed through in vitro cell experiments. After culturing hDPSCs cells with metal extracts, the CCK-8 test results were as follows: Figure 4 The results showed that there was no significant difference in cell proliferation ability between the titanium-zinc alloy group and the pure titanium group and the control group. The results of the 24-hour phalloidin staining experiment, such as Figure 5 The results showed that after being cultured with the titanium-zinc alloy extract, the hDPSCs cells had no significant differences in morphology and pseudopod extension compared with the control group and the pure titanium group, indicating that the material of the present invention has good biosafety.

[0057] Obviously, the above-mentioned embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the embodiments of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the embodiments here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A medical titanium-zinc alloy, characterized in that: It comprises a porous pure titanium bracket and a pure zinc block. The interior of the porous pure titanium bracket is a three-dimensional interconnected structure. The pure zinc block is filled into the gaps of the porous pure titanium bracket by metal infiltration to form a titanium-zinc alloy material.

2. A method for preparing a medical titanium-zinc alloy, characterized in that: The following steps are involved: S1: Pure titanium powder is made into a porous pure titanium stent using selective laser melting technology; S2: placing the porous pure titanium stent in S1 into a mixed solution of hydrofluoric acid, nitric acid and distilled water to remove the unfused titanium powder on the surface, and then washing it with anhydrous ethanol; S3: placing a porous pure titanium support in a crucible, placing a pure zinc block on top of the support, introducing high-purity circulating argon gas by metal molten infiltration, heating to 650-700°C, maintaining for 1-1.5 hours, and then cooling to room temperature with the furnace; S4: After demoulding, a titanium-zinc alloy blank is obtained, and the alloy is cut into shape along the outer boundary of the porous pure titanium bracket.

3. The method for preparing the medical titanium-zinc alloy according to claim 2, characterized in that: The medical pure titanium powder in step S1 is aerosolized pure titanium powder, which is nearly spherical in shape and has a diameter of 15-53 μm; in the laser melting, the powder layer thickness is set to 30 μm, the power is set to 80 W, the laser spot diameter is set to 50 μm, and the scanning speed is set to 600 mm / s.

4. The method for preparing the medical titanium-zinc alloy according to claim 2, characterized in that: The internal unit cell of the porous pure titanium scaffold in step S1 is a rhombic dodecahedron, and the diameter of the prism in each unit is 300-600 μm; the length of the prism is 500-900 μm; the pore size of the porous pure titanium scaffold is 500-1500 μm, and the porosity of the porous pure titanium scaffold is controlled in the range of 30%-80%.

5. The method for preparing the medical titanium-zinc alloy according to claim 2, characterized in that: In the step S2, the mixed aqueous solution of hydrofluoric acid, nitric acid and distilled water is prepared in a ratio of 1:4:5, and the porous pure titanium stent is placed in the mixed aqueous solution of hydrofluoric acid, nitric acid and distilled water and treated with an ultrasonic oscillator for 30 seconds.

6. The method for preparing the medical titanium-zinc alloy according to claim 2, characterized in that: The steps of metal melting and infiltration in step S3 are as follows: place a porous pure titanium bracket in a crucible, and isolate the bracket with graphite paper except for the top; place a pure zinc block on the bracket and cover it with graphite paper; place the crucible on a steel plate, adjust it to a horizontal state, and push it into the furnace to a suitable position. Close the furnace door and test the air tightness. Vacuum for 15 minutes, pump in argon, and close the air inlet valve when the barometer reaches 0, repeat 3 times; adjust the boiler parameters: the starting temperature is 50°C, the temperature is raised to 650-750°C, the heating time is 2 hours, the insulation time is 1-1.5 hours, and then the temperature is lowered to 50°C.

7. The method for preparing a medical titanium-zinc alloy according to claim 2, characterized in that: The titanium-zinc alloy blank in step S4 is cut according to the shape of the pure titanium porous stent, polished with 800, 1000, 1500 and 2000 sandpapers in sequence, then cleaned with anhydrous ethanol by ultrasonic vibration, and dried for later use.

8. An application of the medical titanium-zinc alloy as claimed in claim 1, characterized in that: The medical titanium-zinc alloy is used for bone defect repair, bone reconstruction or bone replacement in orthopedic clinics.

Citation Information

Cited By

  • Craniomaxillofacial dissimilar metal bone implant with antibacterial property and preparation method thereof

    CN119733095A

  • A craniomaxillofacial heterogeneous metal bone implant with antibacterial properties and a preparation method thereof

    CN119733095B